Implementation of Self-Management Techniques in Developing Self-Character in Early Childhood Through Healthy Wednesday and Clean Friday Activities - Arzalia, Firda; Mursid; Shanie, Arsan (Universitas Pendidikan Ganesha, 2025)
Without strong character education, future generations will tend to prioritize personal interests, be dishonest, lack empathy, and lack fighting spirit. The purpose of this study was to analyze self-management techniques for developing self-character in early childhood through Healthy Wednesday and Clean Friday activities. The research approach was qualitative descriptive with a case study method. The main subjects in this study were students, teachers, and parents of students as additional sources of information. Research data were collected through direct observation methods, in-depth interviews, and documentation studies. The research data were analyzed using thematic analysis, which included data reduction, coding, data categorization, and conclusion. Meanwhile, data validation was carried out through triangulation techniques. The results of the study showed that the implementation of self-management techniques applied through the Healthy Wednesday and Clean Friday activity programs was a structured and planned activity program to increase children's awareness and responsibility for the cleanliness and health of the school environment. The study concludes that the implementation of self-management techniques through the Healthy Wednesday and Clean Friday program activities has been empirically proven to improve the character of love for God Almighty, independence, discipline, responsibility, honesty, respect, politeness, cooperation, self-confidence, creativity, leadership, good attitude, and tolerance.